اهمية السياسات الزراعية في تحقيق الاكتفاء الذاتي من السلع الزراعية الغذائية في ليبيا. (Albayan Scientific Journal, 2023)
The main objective of this research paper is to study the relationship between agricultural policies and their relationship to the development and development of the agricultural sector, which contributes to achieving higher levels of self-sufficiency and ensuring food security of locally produced agricultural commodities during the period (1970- 2015). Despite the development witnessed by the agricultural sector in terms of vertical and horizontal expansion, increasing the production rates of many agricultural products and achieving self-sufficiency of some agricultural products in some periods and in varying proportions, Libya, like other developing countries, is still suffering from food shortages. Cover growing domestic demand for most agricultural products, especially cereal and meat crops, due to many administrative and technical constraints. It is expected that the food problem will become more acute in light of the liberalization of global food trade, which will affect Libya due to its large consumption of food imports and the increase in prices in the global market, which means increasing competition between imported food products and local counterparts.